Effect Of Fortivation Calcium-Rich Foodstuffs With Different Concentrations on the Organoleptic Quality of Ikan Tuna Kering Kayu Canned - Laitupa, Ibnu Wahab (Agrikan: Jurnal Agribisnis Perikanan, 2021)
The activity of economic activities in the field of fisheries propagates and grows rapidly not only in fishing activities. Business in the field of processing of fishery products is also growing quite rapidly. This success certainly needs to be accompanied by serious attention to the quality of the products produced. Not only on nutritional content but also on organoleptic parameters. Previous research that has shown positive results on the increase in calcium needs to be continued with organoleptic tests in order to measure the level of consumer interest in the product from aspects of taste, aroma, texture and appearance. Research began from the preparatory stage, the manufacture of fortivation materials, namely tuna bone meal and anchovies, the manufacture of processed products dried tuna wood canned tuna, organoleptic tests and statistical analysis. Fortivation is carried out as many as five treatments, namely without fortivikasi or 0 % (A0), fortivikasi tuna bone meal 3 % (B1), tuna bone meal 6% (B2), anchovies 3% (C1), anchovies flour 6 % (C2). Fortivikasi canned wood dried tuna using bone meal tuna and anchovies with different concentrations, does not have a significant different influence on the quality of appearance, smell, taste and texture on the treatment of B1 and C1 additions of 3% of the total weight of the product with an average value of 8.4 and 8.3 respectively. While in addition to 6% B2 and C2 treatment, it gives a significant influence with an average value of 7.7 and 7.6 treatment, respectively.